Harmonized prevalence estimates of dementia in Europe vary strongly with childhood education - Axel Börsch-Supan; Salima Douhou; Marcela C. Otero; Beatrice Baaba Tawiah (Scientific Reports)
Abstract Up-to-date, strictly cross-nationally comparable and nationally representative data on cognitive health are essential for our understanding of the dementia-related challenges in healthcare, to detect shortcomings in healthcare systems and to design effective prevention strategies. Such data have been missing in Europe. We use the most recent 2022 wave of the strictly harmonized Survey of Health, Ageing and Retirement in Europe (SHARE, 47,773 individuals age 65 and older) to obtain prevalence estimates of mild cognitive impairment and dementia for 27 European countries and Israel in 2022. The novelty of the paper is to validate these estimates using the Harmonized Cognitive Assessment Protocol (HCAP) as a validation tool. These new data exhibit much higher prevalence rates of dementia in the Mediterranean and Southeastern European countries and a much larger variation of cognitive impairment across Europe and Israel than previously known. Dementia prevalence ranges from 4.5% in Switzerland to 22.7% in Spain, MCI prevalence from 17.2% in Sweden to 31.1% in Portugal. Most of this variation can be explained by differences in education when respondents were young. Prevalence rates vary plausibly with other risk factors such as age and comorbidities associated with dementia.